Granice wolności jednostki – problemy metodologiczne i klasyfikacja pojęcia - Górecki, Olgierd (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The term “liberty” is one of the key categories used by researchers on political thought. Its characteristic feature is that despite being intuitively commonly understood, it is difficult to define in a way that is acceptable to all. This article aims to present various positions concerning the scope of human liberty by explicating the methodological issues that arise in the course of analyzing the term “liberty.” To that end, it opens with a discussion of restrictions on external and internal liberty. Next, it voices doubts about whether liberty should be perceived as an actual fact or rather a state of mind. It then progresses to take on the types of relations that constrain the boundaries of liberty, and notes the problems associated with characterizing human liberty in political and legal doctrines that offer a variable normative status of the individual. The latter part of the article presents an innovative classification of individual liberty’s boundaries. The intention behind its drafting is to provide the broadest possible coverage of all potential factors restricting human liberty
Keywords: granice wolności; wolność pozytywna i negatywna; wolność wewnętrzna; wolność; klasyfikacja wolności